1º plano de segurança urbana de São Paulo e o planejamento urbano: análises, diretrizes e propostas - Bifon, Almir (2024)
Introduction: São Paulo is considered to be the largest metropolis in the country, and its crime rate is on the rise. The city government needs to find solutions to problems related to urban security. The municipal executive, showing concern for its citizens with regard to urban security, has included the preparation of a Municipal Urban Security Plan among its priority actions, with a focus on protecting citizens by tackling the causes and consequences of infractions, crimes and violence, including initiatives, objectives and targets. The PSUM is one of the main instruments aimed at seeking a diagnosis to minimize crime rates, through popular participation, creating participatory councils, drawing up guidelines and actions aimed at reducing urban violence, seeking the safety of the population. Given this justification, the research question arises: “How can the 1st Municipal Urban Security Plan (PSUM) integrate urban planning to reduce crime rates?”. The general and specific objectives help to understand the question, with the aim of analyzing the 1st Municipal Urban Security Plan (PSUM), explaining its guidelines and evaluating the integration between Urban Planning, which plays a fundamental role in public security, discussing urban security, and the influence of public policy on the territory with urban and architectural interventions by its public, private and organized society actors that have an impact on reducing crime rates. Methodology: This is a documentary analysis, with extensive bibliographic research, with qualitative characteristics through the collection of information aimed at the proposed objectives. In this context, national and international experiences were presented through successful parallel examples, actions with preventive measures, articulated decisions and the participation of local residents, resulting in the fight against crime. Results: The results indicate that when territorial policy, the integration of the responsible bodies and popular participation occur, the built environment changes, requiring a reading of the entire context in order to understand the entire trajectory of the research.